Quantum dot and manufacturing method for the same

JP2025028913AActive Publication Date: 2025-03-05TOPPAN HOLDINGS INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024202835
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-02-17
Filing Date
2024-11-21
Publication Date
2025-03-05
Estimated Expiration
2040-09-16

AI Technical Summary

Benefits of technology

【0021】 本発明の量子ドットによれば、粒子形状やサイズの揃った量子ドットを合成できるため、蛍光半値幅を狭くでき、高色域化の向上を図ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025028913000001_ABST
    Figure 2025028913000001_ABST
Patent Text Reader

Abstract

To provide a quantum dot that has a narrow fluorescence half-width and a high fluorescence quantum yield, and emits blue fluorescence.SOLUTION: A quantum dot (5) according to the present invention includes at least Zn and Se and does not include Cd, and has a particle diameter of 5 nm or more and 20 nm or less. In addition, the quantum dot (5) according to the present invention includes at least Zn and Se and does not include Cd, and has a fluorescence quantum yield of 5% or more and a fluorescence half-width of 25 nm or less. In the present invention, the fluorescence lifetime can be set to 50 ns or less.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to cadmium-free quantum dots and methods for their manufacture. [Background technology]

[0002] Quantum dots emit fluorescence and are also called fluorescent nanoparticles because their size is on the nanometer order, semiconductor nanoparticles because their composition is derived from semiconductor materials, or nanocrystals because they have a specific crystal structure.

[0003] The performance of quantum dots is expressed by the fluorescence quantum yield (QY) and the fluorescence full width at half maximum (FWHM). When quantum dots are used as wavelength conversion materials in the visible light region, their most significant feature is the wide range of colors that can be expressed, that is, a wide color gamut. In order to achieve a wide color gamut using quantum dots, it is important to narrow the fluorescence full width at half maximum.

[0004] When photoluminescence (PL) is used as the light emission principle for displays using quantum dots, a method is adopted in which a blue LED is used as the backlight to generate excitation light, and quantum dots are used to convert the light into green or red light. On the other hand, when electroluminescence (EL) is used as the light emission principle, or when quantum dots are used to emit all three primary colors by other methods, blue-emitting quantum dots are required. In this case, in order to achieve a wide color gamut, it is necessary that not only green and red but also blue light have a narrow half-width. Therefore, when all three RGB colors are emitted by quantum dots, it is necessary that the fluorescence half-width of blue-emitting quantum dots is narrow.

[0005] Cadmium selenide (CdSe) quantum dots that use cadmium (Cd) are representative of blue quantum dots. However, Cd is internationally regulated, and there have been high barriers to the practical application of materials using CdSe quantum dots.

[0006] On the other hand, the development of quantum dots that do not use Cd is also being considered. For example, the development of chalcopyrite quantum dots such as CuInS2 and AgInS2, and indium phosphide (InP) quantum dots is progressing (see, for example, Patent Document 1). However, the currently developed quantum dots generally have a wide fluorescence half-width and are not suitable as blue-emitting quantum dots.

[0007] In addition, Non-Patent Document 1 listed below describes in detail a method for directly synthesizing ZnSe using diphenylphosphine selenide, which is considered to have a relatively high reactivity with organic zinc compounds, but is not suitable for use as blue-emitting quantum dots.

[0008] Also, a method for synthesizing ZnSe in an aqueous system is reported in the following Non-Patent Document 2. Although the reaction proceeds at low temperatures, the fluorescence half-width is somewhat broad at 30 nm or more, and the fluorescence wavelength is less than 430 nm, making it unsuitable for use as a replacement for conventional blue LEDs to achieve a wide color gamut.

[0009] In addition, the following Non-Patent Document 3 reports a method of synthesizing ZnSe-based quantum dots by forming a precursor such as copper selenide (CuSe) and then cation-exchanging copper with zinc (Zn). However, since the particles of the precursor copper selenide are as large as 15 nm and the reaction conditions for cation-exchanging copper and zinc are not optimal, it can be seen that copper remains in the ZnSe-based quantum dots after cation exchange. From the results of the study of the present invention, it has been found that ZnSe-based quantum dots with residual copper cannot emit light. Alternatively, if copper remains even after emitting light, the emission will be due to defects, and the half-width of the emission spectrum will be 30 nm or more. The particle size of the precursor copper selenide also affects this copper residue, and if the particles are large, copper is likely to remain even after cation exchange, and even if ZnSe can be confirmed by XRD, it is often the case that light does not emit due to a small amount of residual copper. Therefore, Non-Patent Document 3 is cited as an example in which copper remains because the particle size of this precursor and the cation exchange method cannot be optimized. Therefore, blue fluorescence has not been reported. Although there are many reports of the cation exchange method, there are no reports of strong luminescence for the reasons mentioned above. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] International Publication No. 2007 / 060889 Brochure [Non-patent literature]

[0011] [Non-Patent Document 1] Organic Electronics 15 (2014) 126-131 [Non-Patent Document 2] Materials Science and Engineering C 64 (2016) 167-172 [Non-Patent Document 3] J. Am. Chem. Soc.(2015)137 29 9315-9323 Summary of the Invention [Problem to be solved by the invention]

[0012] As described above, although research and development of blue quantum dots is progressing, none of the quantum dots have yet reached a mass-producible level and have the performance to replace Cd-based quantum dots in terms of fluorescence half-width and fluorescence quantum yield.

[0013] The present invention has been made in view of the above-mentioned problems, and has an object to provide quantum dots that emit blue fluorescence with a narrow fluorescence half-width and a high fluorescence quantum yield.

[0014] Another object of the present invention is to provide a quantum dot having a core-shell structure, which has high luminous efficiency and emits blue fluorescence with a narrow fluorescence half-width.

[0015] Another object of the present invention is to provide a method for synthesizing the above quantum dots safely and in a manner that enables mass production. [Means for solving the problem]

[0016] The present invention is characterized in that the core-shell structure has a core containing Zn and Se and a shell containing Zn and S, the particle size is 5 nm or more and 20 nm or less, and the surface of the shell is modified with a halogen.

[0017] In the present invention, the fluorescence half width is preferably 25 nm or less.

[0018] In the present invention, the fluorescent wavelength is preferably in the range of 410 nm or more and 490 nm or less.

[0019] In the present invention, the particle shape may be polygonal.

[0020] The method for producing quantum dots in the present invention is characterized by comprising the steps of synthesizing a copper chalcogenide precursor from an organic copper compound or an inorganic copper compound and an organic chalcogen compound, synthesizing quantum dots having a core-shell structure having a core containing Zn and Se and a shell containing Zn and S using the copper chalcogenide precursor, and then adding a solution containing zinc halide and modifying the surface of the shell with a halogen. In the present invention, it is preferable to perform a metal exchange reaction between Cu and Zn in the copper chalcogenide precursor at a temperature of 150° C. or higher and 300° C. or lower. Effect of the Invention

[0021] According to the quantum dots of the present invention, quantum dots having uniform particle shapes and sizes can be synthesized, so that the fluorescence half-width can be narrowed and an improvement in the color gamut can be achieved.

[0022] Furthermore, according to the method for producing quantum dots of the present invention, it is possible to safely produce quantum dots that have a narrow fluorescence half-width and do not contain Cd, using a method that allows for mass production. [Brief description of the drawings]

[0023] [Figure 1A] FIG. 1A is a schematic diagram of a quantum dot in an embodiment of the present invention. [Figure 1B] FIG. 1B is a schematic diagram of a quantum dot in an embodiment of the present invention. [Diagram 2] 1 is a schematic diagram of an LED device using quantum dots according to an embodiment of the present invention. [Diagram 3] 1 is a vertical sectional view of a display device using an LED device according to an embodiment of the present invention. [Figure 4] 1 shows a photoluminescence (PL) spectrum of ZnSe / ZnS in Example 1. [Diagram 5] 1 shows a PL spectrum of ZnSe / ZnS in Example 2. [Figure 6]1 shows a PL spectrum of ZnSe / ZnS in Example 3. [Figure 7A] 1 is a scanning electron microscopy (SEM) photograph of ZnSe in Example 1. [Figure 7B] FIG. 7B is a schematic diagram of FIG. 7A. [Figure 8A] 1 is a SEM photograph of ZnSe / ZnS in Example 1. [Figure 8B] FIG. 8B is a schematic diagram of FIG. 8A. [Figure 9A] 1 is a SEM photograph of ZnSe in Example 2. [Figure 9B] FIG. 9B is a schematic diagram of FIG. 9A. [Figure 10A] 1 is a SEM photograph of ZnSe / ZnS in Example 2. [Figure 10B] FIG. 10B is a schematic diagram of FIG. 10A. [Figure 11A] 1 is a SEM photograph of ZnSe in Example 3. [Figure 11B] FIG. 11B is a schematic diagram of FIG. 11A. [Figure 12A] 1 is a SEM photograph of ZnSe / ZnS in Example 3. [Figure 12B] FIG. 12B is a schematic diagram of FIG. 12A. [Figure 13] 1 shows X-ray diffraction (XRD) spectra of ZnSe and ZnSe / ZnS in Example 1. [Figure 14] 1 shows XRD spectra of ZnSe and ZnSe / ZnS in Example 2. [Figure 15] 1 shows XRD spectra of ZnSe and ZnSe / ZnS in Example 3. [Figure 16] FIG. 16 is an enlarged view of the XRD spectrum of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] An embodiment of the present invention (hereinafter, abbreviated as "embodiment") will be described in detail below. Note that the present invention is not limited to the following embodiment, and can be practiced in various modifications within the scope of the gist of the present invention.

[0025] 1A and 1B are schematic diagrams of quantum dots in this embodiment. The quantum dots 5 shown in Fig. 1A are nanocrystals that do not contain cadmium (Cd).

[0026] In this embodiment, the quantum dots 5 contain at least zinc (Zn) and selenium (Se), but do not contain Cd. Specifically, the quantum dots are preferably nanocrystals containing Zn and Se, Zn, Se and sulfur (S), or Zn, Se and tellurium (Te).

[0027] The quantum dots 5 have fluorescent properties due to band edge emission, and exhibit a quantum size effect due to their nano-sized particles.

[0028] Here, the term "nanocrystal" refers to nanoparticles having a particle size of about several nm to several tens of nm. In this embodiment, a large number of quantum dots 5 can be produced with a substantially uniform particle size.

[0029] The quantum dots 5 are mainly composed of Zn and Se, Zn, Se and S, or Zn, Se and Te, but may contain elements other than these. However, it is preferable that they do not contain Cd or phosphorus (P). Organic phosphorus compounds are expensive and are easily oxidized in air, making synthesis unstable, which can lead to increased costs, unstable fluorescent properties, and complicated manufacturing processes.

[0030] The quantum dot 5 of this embodiment has a fluorescence half-width of 25 nm or less. The "fluorescence half-width" refers to the full width at half maximum, which indicates the spread of the fluorescence wavelength at half the intensity of the peak value of the fluorescence intensity in the fluorescence spectrum. The fluorescence half-width is preferably 23 nm or less. The fluorescence half-width is more preferably 20 nm or less. The fluorescence half-width is even more preferably 15 nm or less. In this way, in this embodiment, the fluorescence half-width can be narrowed, thereby improving the color gamut.

[0031] In this embodiment, as described later, a reaction system for synthesizing quantum dots 5 is formed by synthesizing a precursor of copper chalcogenide, and then performing a metal exchange reaction on the precursor. By producing quantum dots 5 based on such an indirect synthesis reaction, it is possible to narrow the fluorescence half-width, specifically, to achieve a fluorescence half-width of 25 nm or less.

[0032] It is preferable that a large number of organic ligands 2 are coordinated to the surface of the quantum dots 5. This makes it possible to suppress the aggregation of the quantum dots 5, and to develop the desired optical properties. Furthermore, by adding an amine or thiol-based ligand, it is possible to greatly improve the stability of the quantum dot luminescence properties. The ligands that can be used in the reaction are not particularly limited, but the following ligands are representative examples.

[0033] (1) Aliphatic primary amines Oleylamine: C 18 H 35 NH2, stearyl(octadecyl)amine: C 18 H 37 NH2, dodecyl(lauryl)amine: C 12 H 25 NH2, Decylamine: C 10 H 21 NH2, Octylamine: C8H 17 NH2 (2) Fatty acid type Oleic acid: C 17 H 33COOH, stearic acid: C 17 H 35 COOH, Palmitic acid: C 15 H 31 COOH, myristic acid: C 13 H 27 COOH, lauryl(dodecanoic) acid: C 11 H 23 COOH, Decanoic acid: C9H 19 COOH, Octanoic acid: C7H 15 COOH (3) Thiols Octadecanethiol: C 18 H 37 SH, hexanedecanethiol: C 16 H 33 SH, tetradecanethiol: C 14 H 29 SH, dodecanethiol: C 12 H 25 SH, decanethiol: C 10 H 21 SH, Octanethiol: C8H 17 SH (4) Phosphine Trioctylphosphine: (C8H 17 )3P, triphenylphosphine: (C6H5)3P, tributylphosphine: (C4H9)3P (5) Phosphine oxides Trioctylphosphine oxide: (C8H 17 )3P=O, triphenylphosphine oxide: (C6H5)3P=O, tributylphosphine oxide: (C4H9)3P=O

[0034] The quantum dots 5 in this embodiment have a fluorescence quantum yield of 5% or more. The fluorescence quantum yield is preferably 20% or more, more preferably 50% or more, and even more preferably 80% or more. In this way, this embodiment can increase the fluorescence quantum yield of the quantum dots.

[0035] In this embodiment, the particle size of the quantum dots 5 can be adjusted to 5 nm or more and 20 nm or less. In this embodiment, the particle size of the quantum dots 5 can be preferably 15 nm or less, and more preferably 10 nm or less. In this way, in this embodiment, the particle size of the quantum dots 5 can be reduced, and the variation in the particle size of each quantum dot 5 can be reduced, and quantum dots 5 of uniform size can be obtained. As a result, in this embodiment, the fluorescence half width of the quantum dots 5 can be narrowed to 25 nm or less as described above, and the color gamut can be improved.

[0036] In addition, in this embodiment, the fluorescence lifetime of the quantum dots 5 can be set to 50 ns or less. In this embodiment, the fluorescence lifetime can also be adjusted to 40 ns or less, or even 30 ns or less. In this way, in this embodiment, the fluorescence lifetime can be shortened, but can also be extended to about 50 ns, making it possible to adjust the fluorescence lifetime depending on the application.

[0037] In this embodiment, the fluorescence wavelength can be freely controlled to about 410 nm or more and 490 nm or less. The quantum dots 5 in this embodiment use chalcogen elements other than Zn, and specifically, are solid solutions based on ZnSe. In this embodiment, the fluorescence wavelength can be controlled by adjusting the particle size of the quantum dots 5 and the composition of the quantum dots 5. In this embodiment, the fluorescence wavelength can be preferably 430 nm or more, and more preferably 450 nm or more. In addition, in the quantum dots 5 based on ZnSeTe, the fluorescence wavelength can be 450 nm or more and 490 nm or less. In addition, the fluorescence wavelength can be 480 nm or less, or 470 nm or less.

[0038] In this way, the quantum dots 5 of this embodiment can control the fluorescence wavelength to blue.

[0039] The quantum dot 5 shown in Fig. 1B has a core-shell structure having a core 5a and a shell 5b coated on the surface of the core 5a. As shown in Fig. 1B, it is preferable that a large number of organic ligands 2 are coordinated to the surface of the quantum dot 5.

[0040] In this embodiment, the above-mentioned fluorescence half width and fluorescence quantum yield can be obtained even in the core-shell structure. That is, in the quantum dot 5 having the core-shell structure shown in FIG. 1B, the fluorescence half width can be set to 25 nm or less. Also, the fluorescence quantum yield can be set to 5% or more. The above-mentioned ranges can be applied as the preferable ranges of the fluorescence half width and the fluorescence quantum yield.

[0041] The particle size of the quantum dots 5 with the core-shell structure shown in Fig. 1B is 5 nm or more and 20 nm or less. Although the particle size is somewhat larger by using the core-shell structure than the structure of the single core shown in Fig. 1A, the particle size can be kept at 20 nm or less, and it is possible to obtain quantum dots 5 with the core-shell structure having a very small particle size.

[0042] The core 5a of the quantum dot 5 shown in Fig. 1B is the nanocrystal shown in Fig. 1A. Therefore, the core 5a is preferably made of ZnSe, ZnSeS, or ZnSeTe. The shell 5b does not contain Cd, like the core 5a. The shell 5b may be made of any material, such as ZnS.

[0043] The shell 5b may be in a state of being solidified on the surface of the core 5a. In FIG. 1B, the boundary between the core 5a and the shell 5b is shown by a dotted line, but this means that the boundary between the core 5a and the shell 5b may or may not be confirmed by analysis. In this embodiment, the core 5a alone has the characteristic of emitting fluorescence.

[0044] The quantum dot 5 with the core-shell structure shown in FIG. 1B can freely control the fluorescence wavelength to about 410 nm or more and 490 nm or less, similarly to FIG. 1A. In this embodiment, the fluorescence wavelength can be controlled to blue. The quantum dot 5 with the core-shell structure can also have a fluorescence lifetime of 50 ns, but the core-shell structure can shorten the fluorescence lifetime compared to a single core 5a with the same composition and particle size.

[0045] Next, a method for producing the quantum dots 5 of this embodiment will be described. First, in this embodiment, a copper chalcogenide precursor is synthesized from an organic copper compound or an inorganic copper compound and an organic chalcogen compound. Specifically, the copper chalcogenide precursor is preferably Cu2Se, Cu2SeS, Cu2SeTe, Cu2SeTeS, CuSe, CuSeS, CuSeTe, or CuSeTeS.

[0046] Here, in this embodiment, the Cu raw material is not particularly limited, but for example, the following organic copper reagents or inorganic copper reagents can be used. That is, as acetates, copper acetate (I): Cu(OAc) and copper acetate (II): Cu(OAc)2, as fatty acid salts, copper stearate: Cu(OC(=O)C 17 H 35 )2, Copper oleate: Cu(OC(=O)C 17 H 33 )2, Copper myristate: Cu(OC(=O)C 13 H 27 )2, Copper dodecanoate: Cu(OC(=O)C 11 H 23 )2, copper acetylacetonate: Cu(acac)2, and both monovalent and divalent halides can be used, such as copper chloride(I): CuCl, copper chloride(II): CuCl2, copper bromide(I): CuBr, copper bromide(II): CuBr2, copper iodide(I): CuI, and copper iodide(II): CuI2.

[0047] In this embodiment, the Se raw material is an organic selenium compound (organic chalcogenide). The structure of the compound is not particularly limited, but for example, trioctylphosphine selenide: (C8H2O3) in which Se is dissolved in trioctylphosphine is used. 17 )3P=Se, or tributylphosphine selenide: (C4H9)3P=Se obtained by dissolving Se in tributylphosphine, etc. Alternatively, a solution in which Se is dissolved at high temperature in a high boiling point solvent such as a long chain hydrocarbon like octadecene (Se-ODE), or a solution in which Se is dissolved in a mixture of oleylamine and dodecanethiol (Se-DDT / OLAm) can be used.

[0048] In this embodiment, Te is used as a raw material in the form of an organic tellurium compound (organic chalcogen compound). The structure of the compound is not particularly limited, but for example, trioctylphosphine telluride: (C8H 17 )3P=Te, or tributylphosphine telluride (C4H9)3P=Te in which Te is dissolved in tributylphosphine, etc. Also, it is possible to use dialkyl ditellurides (R2Te2) such as diphenyl ditelluride (C6H5)2Te2, or a solution in which Te is dissolved in a mixture of oleylamine and dodecanethiol (Te-DDT / OLAm), etc.

[0049] In this embodiment, an organic copper compound or an inorganic copper compound is mixed with an organic chalcogen compound and dissolved. As the solvent, octadecene can be used as a high boiling point saturated or unsaturated hydrocarbon. In addition, t-butylbenzene can be used as an aromatic high boiling point solvent, butyl butyrate: C4H9COOC4H9, benzyl butyrate: C6H5CH2COOC4H9, etc. can be used as a high boiling point ester solvent, but it is also possible to use an aliphatic amine compound, a fatty acid compound, an aliphatic phosphorus compound, or a mixture of these as the solvent.

[0050] At this time, the copper chalcogenide precursor is synthesized at a reaction temperature set in the range of 140° C. to 250° C. Note that the reaction temperature is preferably lower, 140° C. to 220° C., and more preferably lower, 140° C. to 200° C.

[0051] In addition, in this embodiment, the reaction method is not particularly limited, but in order to obtain quantum dots with a narrow fluorescence half-width, it is important to synthesize Cu2Se, Cu2SeS, Cu2SeTe, and Cu2SeTeS with uniform particle sizes.

[0052] In addition, the particle size of the copper chalcogenide precursor such as Cu2Se, Cu2SeS, Cu2SeTe, and Cu2SeTeS is preferably 20 nm or less, more preferably 15 nm or less, and even more preferably 10 nm or less. The wavelength of the ZnSe quantum dot can be controlled by the composition and particle size of the copper chalcogenide precursor. Therefore, it is important to perform appropriate particle size control.

[0053] In this embodiment, in order to obtain quantum dots with a narrower fluorescence half-width as the core, it is important to dissolve S in the core. For this reason, it is preferable to add a thiol in the synthesis of the precursor Cu2Se or Cu2SeTe. In order to obtain quantum dots with a narrower fluorescence half-width, it is more preferable to use Se-DDT / OLAm as the Se raw material. Although the thiol is not particularly limited, for example, octadecanethiol:C 18 H 37 SH, hexanedecanethiol: C 16 H 33 SH, tetradecanethiol: C 14 H 29 SH, dodecanethiol: C 12 H 25 SH, decanethiol: C 10 H 21 SH, Octanethiol: C8H 17 SH, etc.

[0054] Next, an organic zinc compound or an inorganic zinc compound is prepared as a raw material for ZnSe, ZnSeS, ZnSeTe, or ZnSeTeS. The organic zinc compound or the inorganic zinc compound is a raw material that is stable even in air and easy to handle. The structure of the organic zinc compound or the inorganic zinc compound is not particularly limited, but in order to efficiently carry out the metal exchange reaction, it is preferable to use a zinc compound with high ionicity. For example, the organic zinc compound and the inorganic zinc compound shown below can be used. That is, as acetates, zinc acetate: Zn(OAc)2, zinc nitrate: Zn(NO3)2, as fatty acid salts, zinc stearate: Zn(OC(=O)C 17 H 35 )2, Zinc oleate: Zn(OC(=O)C 17 H 33 )2, Zinc palmitate: Zn(OC(=O)C 15 H 31 )2, Zinc myristate: Zn(OC(=O)C 13 H 27 )2, Zinc dodecanoate: Zn(OC(=O)C 11 H 23 )2, zinc acetylacetonate: Zn(acac)2, and as halides, zinc chloride: ZnCl2, zinc bromide: ZnBr2, zinc iodide: ZnI2, and as zinc carbamates, zinc diethyldithiocarbamate: Zn(SC(=S)N(C2H5)2)2, zinc dimethyldithiocarbamate: Zn(SC(=S)N(CH3)2)2, zinc dibutyldithiocarbamate: Zn(SC(=S)N(C4H9)2)2, etc. can be used.

[0055] Next, the organic zinc compound or inorganic zinc compound is added to the reaction solution in which the copper chalcogenide precursor is synthesized. This causes a metal exchange reaction between Cu of the copper chalcogenide and Zn. The metal exchange reaction is preferably caused at a temperature of 150°C or higher and 300°C or lower. It is also more preferable to cause the metal exchange reaction at a lower temperature, 150°C or higher and 280°C or lower, more preferably 150°C or higher and 250°C or lower.

[0056] In this embodiment, the metal exchange reaction between Cu and Zn proceeds quantitatively, and it is preferable that the precursor Cu is not contained in the nanocrystal. If the precursor Cu remains in the nanocrystal, it acts as a dopant and emits light by a different emission mechanism, widening the fluorescence half-width. The amount of this remaining Cu is preferably 100 ppm or less, more preferably 50 ppm or less, and ideally 10 ppm or less relative to Zn.

[0057] In this embodiment, the ZnSe quantum dots synthesized by the cation exchange method tend to have a higher Cu residual amount than the ZnSe quantum dots synthesized by the direct method, but good luminescence characteristics can be obtained even if the Cu content is about 1 to 10 ppm relative to Zn. It is possible to determine whether the quantum dots are synthesized by the cation exchange method based on the Cu residual amount. That is, by synthesizing by the cation exchange method, the particle size can be controlled with the copper chalcogenide precursor, and quantum dots that are inherently difficult to react can be synthesized, so the Cu residual amount is advantageous in determining whether the cation exchange method has been used.

[0058] In addition, in this embodiment, when metal exchange is performed, a compound is needed that has an auxiliary role of liberating the metal of the copper chalcogenide precursor into the reaction solution by coordination or chelation or the like.

[0059] The compound having the above-mentioned function is a ligand capable of forming a complex with Cu. For example, phosphorus-based ligands, amine-based ligands, and sulfur-based ligands are preferable, and among them, phosphorus-based ligands are more preferable due to their high efficiency.

[0060] This allows the metal exchange between Cu and Zn to be properly performed, and quantum dots with narrow fluorescence half-widths based on Zn and Se can be produced. In this embodiment, the cation exchange method described above allows the mass production of quantum dots compared to the direct synthesis method.

[0061] That is, in the direct synthesis method, an organic zinc compound such as diethylzinc (Et2Zn) is used to increase the reactivity of the Zn raw material. However, diethylzinc is highly reactive and ignites in air, so it must be handled under an inert gas flow, making it difficult to handle and store as a raw material, and reactions using it involve the risk of heat generation and fire, making it unsuitable for mass production. Similarly, reactions using selenium hydride (H2Se) to increase the reactivity of the Se raw material are also unsuitable for mass production from the standpoint of toxicity and safety.

[0062] Furthermore, in reaction systems using highly reactive Zn and Se raw materials as described above, ZnSe is produced, but particle generation is not controlled, resulting in a broad fluorescence half-width of the resulting ZnSe.

[0063] In contrast, in this embodiment, a copper chalcogenide precursor is synthesized from an organic copper compound or an inorganic copper compound and an organic chalcogen compound, and quantum dots are synthesized by metal exchange using the copper chalcogenide precursor. In this way, in this embodiment, quantum dots are synthesized first through the synthesis of a copper chalcogenide precursor, and are not directly synthesized. By such indirect synthesis, it is not necessary to use a reagent that is too highly reactive and dangerous to handle, and it is possible to safely and stably synthesize ZnSe-based quantum dots with narrow fluorescence half-width.

[0064] In this embodiment, it is possible to obtain quantum dots having a desired composition and particle size by performing metal exchange between Cu and Zn in one pot without isolating and purifying the copper chalcogenide precursor. On the other hand, the copper chalcogenide precursor may be used after being isolated and purified once.

[0065] Furthermore, in this embodiment, the synthesized quantum dots exhibit fluorescent properties without undergoing various treatments such as washing, isolation and purification, coating treatment, and ligand exchange.

[0066] However, as shown in Fig. 1B, the fluorescence quantum yield can be further increased by covering the core 5a made of nanocrystals such as ZnSe, ZnSeS, ZnSeTe, or ZnSeTeS with a shell 5b of ZnS, ZnSeS, etc. Furthermore, by using a core-shell structure, the fluorescence lifetime can be made shorter than that before the shell covering.

[0067] Also, as shown in Fig. 1B, by covering the core 5a with the shell 5b, it is possible to make the wavelength shorter or longer than that of the core 5a. For example, when the particle size of the core 5a is small, covering the shell 5b tends to make the wavelength longer, but when the particle size of the core 5a is large, covering the shell 5b tends to make the wavelength shorter. The magnitude of the wavelength change value also differs depending on the conditions of covering the shell 5b.

[0068] Furthermore, by adding ZnSe, ZnSeS, ZnSeTe, or ZnSeTeS, which is the same raw material, to the core 5a made of nanocrystals such as ZnSe, ZnSeS, ZnSeTe, or ZnSeTeS obtained by the cation exchange method, it is possible to obtain the core 5a of the quantum dot 5 whose particle size is changed to an arbitrary size while keeping the particle size uniform. Therefore, it is easy to control the wavelength from 410 nm to 490 nm while maintaining the fluorescence half-width at 25 nm or less.

[0069] In addition, in this embodiment, the core-shell structure can be synthesized at the stage of the copper chalcogenide precursor. For example, Cu2Se / Cu2S can be synthesized by continuously adding S raw material to the copper chalcogenide precursor Cu2Se, and then ZnSe / ZnS can be obtained by metal exchange between Cu and Zn.

[0070] In the present embodiment, the S raw material used for the core-shell structure is not particularly limited, but the following raw materials are typical examples.

[0071] That is, as a thiol, octadecanethiol: C 18 H37 SH, hexanedecanethiol: C 16 H 33 SH, tetradecanethiol: C 14 H 29 SH, dodecanethiol: C 12 H 25 SH, decanethiol: C 10 H 21 SH, Octanethiol: C8H 17 Examples of sulfur that can be used include a solution of sulfur dissolved in a high-boiling solvent such as SH, benzenethiol: CHSH, or a long-chain phosphine-based hydrocarbon such as trioctylphosphine (S-TOP), a solution of sulfur dissolved in a high-boiling solvent such as a long-chain hydrocarbon such as octadecene (S-ODE), or a solution of sulfur dissolved in a mixture of oleylamine and dodecanethiol (S-DDT / OLAm).

[0072] Depending on the S raw material used, the reactivity differs, and as a result, the coating thickness of the shell 5b (e.g., ZnS) can be varied. The reactivity of the thiol system is proportional to its decomposition rate, and the reactivity of S-TOP or S-ODE changes in proportion to its stability. Thus, by using different S raw materials, it is possible to control the coating thickness of the shell 5b, and the final fluorescence quantum yield can also be controlled.

[0073] In this embodiment, the Zn raw material used for the core-shell structure can be the raw material described above.

[0074] The optimal coating thickness can also be calculated from the change in fluorescence lifetime. As the number of times the coating material is added increases, the particle size increases and the fluorescence lifetime gradually decreases. At the same time, the fluorescence quantum yield also increases, so it was found that the fluorescence quantum yield is highest when the fluorescence lifetime is shortest.

[0075] In this embodiment, the less the amine-based solvent used in coating the shell 5b, the easier it is to coat the shell 5b and the better the luminescence characteristics can be obtained. Furthermore, the luminescence characteristics after coating the shell 5b differ depending on the ratio of the amine-based solvent to the carboxylic acid-based or phosphine-based solvent.

[0076] Furthermore, the quantum dots 5 synthesized by the manufacturing method of this embodiment can be aggregated by adding a polar solvent such as methanol, ethanol, or acetone, and the quantum dots 5 and unreacted raw materials can be separated and collected. The collected quantum dots 5 are dispersed again by adding toluene, hexane, or the like. By adding a solvent that serves as a ligand to this redispersed solution, it is possible to further improve the luminescence characteristics and improve the stability of the luminescence characteristics. The change in the luminescence characteristics caused by adding this ligand is greatly different depending on whether or not the shell 5b is coated, and in this embodiment, the quantum dots 5 coated with the shell 5b can be improved in particular in fluorescence stability by adding a thiol-based ligand.

[0077] The applications of the quantum dots 5 shown in FIGS. 1A and 1B are not particularly limited. For example, the quantum dots 5 of this embodiment that emit blue fluorescence can be applied to wavelength conversion members, lighting members, backlight devices, display devices, and the like.

[0078] The quantum dots 5 of this embodiment are applied to a wavelength conversion member, an illumination member, a backlight device, a display device, etc., and when photoluminescence (PL) is used as the light emission principle, blue fluorescence can be emitted by UV irradiation from a light source. Alternatively, when electroluminescence (EL) is used as the light emission principle, or when quantum dots emit all three primary colors by other methods, the quantum dots 5 of this embodiment can be used as a light emitting element that emits blue fluorescence. In this embodiment, a light emitting element (full color LED) including quantum dots 5 of this embodiment that emit blue fluorescence, together with quantum dots that emit green fluorescence and quantum dots that emit red fluorescence, can be used to emit white light.

[0079] Fig. 2 is a schematic diagram of an LED device using quantum dots according to this embodiment. As shown in Fig. 2, the LED device 1 according to this embodiment is configured to include a storage case 2 having a bottom surface 2a and a side wall 2b surrounding the bottom surface 2a, an LED chip (light-emitting element) 3 arranged on the bottom surface 2a of the storage case 2, and a fluorescent layer 4 filled in the storage case 2 and sealing the upper surface side of the LED chip 3. Here, the upper surface side refers to the direction in which light emitted by the LED chip 3 is emitted from the storage case 2, and indicates the opposite direction to the bottom surface 2a with respect to the LED chip 3.

[0080] The LED chip 3 is disposed on a base wiring board (not shown), which may constitute the bottom surface of the storage case 2. The base board may be, for example, a base material such as glass epoxy resin having a wiring pattern formed thereon.

[0081] The LED chip 3 is a semiconductor element that emits light when a voltage is applied in the forward direction, and has a basic configuration in which a P-type semiconductor layer and an N-type semiconductor layer are PN junctioned.

[0082] As shown in FIG. 2, the fluorescent layer 4 is formed from a resin 6 in which a large number of quantum dots 5 are dispersed.

[0083] The resin composition in this embodiment in which the quantum dots 5 are dispersed may contain the quantum dots 5 and a fluorescent material other than the quantum dots 5. The fluorescent material may be a sialon-based material or a KSF (K2SiF6:Mn 4+ ) red phosphor, but the material is not particularly limited.

[0084] The resin 6 constituting the fluorescent layer 4 is not particularly limited, but examples of the resin that can be used include polypropylene (PP), polystyrene (PS), acrylic resin, methacrylic resin, MS resin, polyvinyl chloride (PVC), polycarbonate (PC), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polymethylpentene, liquid crystal polymer, epoxy resin, silicone resin, and mixtures of these.

[0085] The LED device using the quantum dots of this embodiment can be applied to a display device. Fig. 3 is a vertical cross-sectional view of a display device using the LED device shown in Fig. 2. As shown in Fig. 3, a display device 50 is configured to have a plurality of LED devices 20 and a display unit 54 such as a liquid crystal display facing each LED device 20. Each LED device 20 is disposed on the back side of the display unit 54. Each LED device 20 has a structure in which an LED chip is sealed with a resin in which a large number of quantum dots 5 are diffused, similar to the LED device 1 shown in Fig. 2.

[0086] As shown in Fig. 3, the LED devices 20 are supported by a support 52. The LED devices 20 are arranged at predetermined intervals. The LED devices 20 and the support 52 constitute a backlight 55 for a display unit 54. The support 52 is not particularly limited in shape or material and may be in the form of a sheet, plate, or case. As shown in Fig. 3, a light diffusion plate 53 or the like may be interposed between the backlight 55 and the display unit 54.

[0087] By applying the quantum dot 5 having a narrow fluorescence half-width in this embodiment to the LED device shown in FIG. 2 or the display device shown in FIG. 3, it is possible to effectively improve the light-emitting characteristics of the device.

[0088] Furthermore, a resin composition in which the quantum dots 5 of this embodiment are dispersed in a resin can be formed into a sheet or film. Such a sheet or film can be incorporated into, for example, a backlight device.

[0089] In addition, in this embodiment, a wavelength conversion member in which a plurality of quantum dots are dispersed in a resin can be formed from a molded body. For example, a molded body in which quantum dots are dispersed in a resin is stored in a container having a storage space by pressing or the like. At this time, it is preferable that the refractive index of the molded body is smaller than the refractive index of the container. As a result, a part of the light that enters the molded body is totally reflected by the inner wall of the container. Therefore, it is possible to reduce the beam of light leaking from the side of the container to the outside. In this way, by applying the quantum dots with a narrow fluorescence half-width in this embodiment to wavelength conversion members, lighting members, backlight devices, display devices, and the like, it is possible to effectively improve the light emission characteristics. EXAMPLES

[0090] The effects of the present invention will be described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0091] In the present invention, the following raw materials were used to synthesize the Cd-free quantum dots, and the following measuring instruments were used to evaluate the synthesized quantum dots.

[0092] <Raw materials> Anhydrous copper acetate: Wako Pure Chemical Industries, Ltd. Octadecene: Manufactured by Idemitsu Kosan Co., Ltd. Oleylamine: Farmin, manufactured by Kao Corporation Oleic acid: Lunac OV manufactured by Kao Corporation Dodecanethiol (Se-DDT): Kao Corporation Thiokalcol 20 Trioctylphosphine: manufactured by Hokko Chemical Co., Ltd. Anhydrous zinc acetate: Kishida Chemical Co., Ltd. Selenium (4N: 99.99%): Shinko Chemical Co., Ltd. Sulfur: Kishida Chemical Co., Ltd. <Measuring equipment> Fluorescence spectrometer: JASCO F-2700 UV-Visible spectrophotometer: Hitachi V-770 Quantum yield measurement device: Otsuka Electronics Co., Ltd. QE-1100 X-ray diffraction device (XRD): Bruker D2 PHASER Scanning electron microscope (SEM): Hitachi SU9000 Fluorescence lifetime measurement device: Hamamatsu Photonics C11367

[0093] [Example 1] In a 300 mL reaction vessel, 2546 mg of anhydrous copper acetate (Cu(OAc)), 28.5 mL of oleylamine (OLAm) and 46.5 mL of octadecene (ODE) were placed, and the mixture was heated at 150° C. for 20 minutes under an inert gas (N2) atmosphere while stirring to dissolve the raw materials.

[0094] To this solution, 8.4 mL of a Se-DDT / OLAm solution (0.285 M) was added, and the mixture was heated with stirring at 150° C. for 10 minutes. The resulting reaction solution (CuSe) was cooled to room temperature.

[0095] Then, 24.092 g of anhydrous zinc acetate: Zn(OAc), 60 mL of trioctylphosphine: TOP, and 2.4 mL of oleylamine: OLAm were added to the Cu2Se reaction solution, and the mixture was heated under inert gas (N2) atmosphere at 180°C for 30 minutes with stirring. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0096] Ethanol was added to the reaction solution cooled to room temperature to generate a precipitate, which was then centrifuged to recover the precipitate, and 72 ml of octadecene (ODE) was added to disperse the precipitate.

[0097] Then, 24.092 g of anhydrous zinc acetate (Zn(OAc)), 30 mL of trioctylphosphine (TOP), 3 mL of oleylamine (OLAm) and 36 mL of oleic acid were added to 72 mL of the ZnSe-ODE solution, and the mixture was heated under inert gas (N2) atmosphere at 280°C for 30 minutes with stirring. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0098] The reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were a fluorescence wavelength of about 430.5 nm and a fluorescence half-width of about 15 nm.

[0099] The reaction solution was measured using a quantum efficiency measurement system. The fluorescence quantum yield was found to be about 30%. The fluorescence lifetime was also measured to be 48 ns.

[0100] The resulting dispersion of ZnSe particles was measured using a scanning electron microscope (SEM) and an X-ray diffraction (XRD) device. Figure 7A shows the results of the measurement using a scanning electron microscope (SEM), Figure 7B shows a schematic diagram of Figure 7A, and the dotted line in Figure 13 shows the results of the measurement using X-ray diffraction (XRD). The SEM results showed that the particle size was about 5 nm. The XRD results also showed that the crystals were cubic, and the position of the crystal peaks was consistent with that of ZnSe.

[0101] Ethanol was added to 47 ml of the ZnSe reaction solution obtained separately from the above to generate a precipitate, which was then centrifuged to recover the precipitate, and 35 ml of octadecene (ODE) was added to disperse the precipitate.

[0102] 35 mL of the dispersed ZnSe-ODE solution was heated with stirring at 310° C. for 20 minutes under an inert gas (N 2 ) atmosphere.

[0103] To this solution, 1.1 mL of a mixture of 2.2 mL of S-TOP solution (2.2 M) and 11 mL of zinc oleate: Zn(OLAc)2 solution (0.8 M) was added, and the mixture was heated at 310°C for 20 minutes with stirring. This operation was repeated 12 times. The resulting reaction solution (ZnSe / ZnS) was cooled to room temperature.

[0104] Ethanol was added to the resulting reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and hexane was added to disperse the precipitate.

[0105] The hexane-dispersed ZnSe / ZnS was measured using a fluorescence spectrometer. As a result, the optical characteristics were obtained as shown in Figure 4, with a fluorescence wavelength of about 423 nm and a fluorescence half-width of about 15 nm.

[0106] The same solution was measured using a quantum efficiency measurement system, and the fluorescence quantum yield was found to be about 60%. The fluorescence lifetime was also measured to be 44 ns.

[0107] The obtained dispersion of ZnSe / ZnS particles was measured using a scanning electron microscope (SEM) and an X-ray diffraction (XRD) device. Figure 8A shows the results of the measurement using a scanning electron microscope (SEM), Figure 8B shows a schematic diagram of Figure 8A, and the solid line in Figure 13 shows the results of the measurement using X-ray diffraction (XRD). From the results of SEM, the particle size was about 12 nm. From the results of XRD, it was found that the crystals were cubic and that the maximum peak intensity was shifted 1.1° to the high-angle side from the crystal peak position of ZnSe.

[0108] [Example 2] In a 100 mL reaction vessel, 291 mg of anhydrous copper acetate (Cu(OAc)), 4.8 mL of oleylamine (OLAm), and 7.75 mL of octadecene (ODE) were placed, and the mixture was heated at 150° C. for 5 minutes under an inert gas (N2) atmosphere while stirring to dissolve the raw materials.

[0109] To this solution, 1.4 mL of a Se-DDT / OLAm solution (0.285 M) was added, and the mixture was heated with stirring at 150° C. for 30 minutes. The resulting reaction solution (Cu2Se) was cooled to room temperature.

[0110] Then, 682 mg of anhydrous zinc acetate: Zn(OAc), 10 mL of trioctylphosphine: TOP, and 0.4 mL of oleylamine: OLAm were added to the Cu2Se reaction solution, and the mixture was heated under inert gas (N2) atmosphere at 180°C for 10 minutes with stirring. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0111] Ethanol was added to the reaction solution cooled to room temperature to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 ml of octadecene (ODE) was added to disperse the precipitate.

[0112] Then, 2682 mg of anhydrous zinc acetate: Zn(OAc), 5 mL of trioctylphosphine: TOP, 0.5 mL of oleylamine: OLAm, and 6 mL of oleic acid: OLAc were added to 12 mL of the ZnSe-ODE solution, and the mixture was heated under inert gas (N2) atmosphere at 280°C for 30 minutes with stirring. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0113] The reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were a fluorescence wavelength of about 437 nm and a fluorescence half-width of about 15 nm.

[0114] Ethanol was added to the resulting reaction solution (several ml) to generate a precipitate, which was then centrifuged to recover the precipitate, which was then dispersed in hexane.

[0115] ZnSe dispersed in hexane was measured using a quantum efficiency measurement system. The fluorescence quantum yield was found to be about 37%. The fluorescence lifetime was also measured to be 13 ns.

[0116] In addition, measurements were made using a scanning electron microscope (SEM) and an X-ray diffraction (XRD) device. Figure 9A shows the results of the scanning electron microscope (SEM), Figure 9B shows a schematic diagram of Figure 9A, and the dotted line in Figure 14 shows the results of the X-ray diffraction (XRD) measurements. From the SEM results, the grain size was approximately 6.0 nm. From the XRD results, it was found that the crystals were cubic, and the position of the crystal peaks was consistent with that of ZnSe.

[0117] Ethanol was added to 23 ml of the ZnSe reaction solution obtained separately from the above to generate a precipitate, which was then centrifuged to recover the precipitate, and 17.5 ml of octadecene:ODE was added to disperse the precipitate.

[0118] 1 mL of oleic acid (OLAc) and 2 mL of trioctylphosphine (TOP) were added to 17.5 mL of the dispersed ZnSe-ODE solution, and the mixture was heated with stirring at 320° C. for 10 minutes in an inert gas (N 2 ) atmosphere.

[0119] To this solution, 0.5 mL of a mixture of 1 mL of S-TOP solution (1 M) and 5 mL of zinc oleate: Zn(OLAc)2 solution (0.4 M) was added, and the mixture was heated at 320° C. for 10 minutes with stirring. This operation was repeated 8 times.

[0120] Then, 2 ml of oleic acid (OLAc) was added and reacted at 320° C. for 10 minutes, and 2 ml of trioctylphosphine (TOP) was added and heated with stirring for 10 minutes at 320° C. The resulting reaction solution (ZnSe / ZnS) was cooled to room temperature.

[0121] The reaction solution thus obtained was measured using a fluorescence spectrometer, and as a result, the optical characteristics obtained were a fluorescence wavelength of about 435 nm and a fluorescence half-width of about 16 nm, as shown in FIG.

[0122] Ethanol was added to the resulting reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and hexane was added to disperse the precipitate.

[0123] ZnSe / ZnS dispersed in hexane was measured using a quantum efficiency measurement system. The fluorescence quantum yield was about 81%. The fluorescence lifetime was measured and was 12 ns.

[0124] Measurements were also performed using a scanning electron microscope (SEM) and an X-ray diffraction (XRD) device. Figure 10A shows the results of the measurement using a scanning electron microscope (SEM), Figure 10B shows a schematic diagram of Figure 10A, and the solid line in Figure 14 shows the results of the measurement using X-ray diffraction (XRD). From the results of SEM, the grain size was approximately 8.5 nm. From the results of XRD, it was found that the crystals were cubic and that the maximum peak intensity was shifted 0.4° to the high-angle side from the crystal peak position of ZnSe.

[0125] [Example 3] In a 100 mL reaction vessel, 291 mg of anhydrous copper acetate (Cu(OAc)), 4.8 mL of oleylamine (OLAm), and 7.75 mL of octadecene (ODE) were placed, and the mixture was heated at 170° C. for 5 minutes under an inert gas (N2) atmosphere while stirring to dissolve the raw materials.

[0126] To this solution, 1.4 mL of a Se-DDT / OLAm solution (0.285 M) was added, and the mixture was heated with stirring at 170° C. for 30 minutes. The resulting reaction solution (CuSe) was cooled to room temperature.

[0127] Then, 2922 mg of anhydrous zinc acetate: Zn(OAc), 10 mL of trioctylphosphine: TOP, and 0.4 mL of oleylamine: OLAm were added to the Cu2Se reaction solution, and the mixture was heated under inert gas (N2) atmosphere at 180°C for 30 minutes with stirring. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0128] Ethanol was added to the reaction solution cooled to room temperature to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 ml of octadecene (ODE) was added to disperse the precipitate.

[0129] Then, 2922 mg of anhydrous zinc acetate: Zn(OAc), 5 mL of trioctylphosphine: TOP, 0.5 mL of oleylamine: OLAm, and 3 mL of oleic acid: OLAc were added to 12 mL of the ZnSe-ODE solution, and the mixture was heated under inert gas (N2) atmosphere at 280°C for 20 minutes with stirring. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0130] The reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were a fluorescence wavelength of about 448 nm and a fluorescence half-width of about 15 nm.

[0131] Ethanol was added to the resulting reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and hexane was added to disperse the precipitate.

[0132] ZnSe dispersed in hexane was measured using a quantum efficiency measurement system. The fluorescence quantum yield was about 6%. The fluorescence lifetime was also measured and was found to be 25ns.

[0133] In addition, measurements were made using a scanning electron microscope (SEM) and an X-ray diffraction (XRD) device. FIG. 11A shows the results of the measurement using a scanning electron microscope (SEM), FIG. 11B shows a schematic diagram of FIG. 11A, and the dotted line in FIG. 15 shows the results of the measurement using X-ray diffraction (XRD). From the results of SEM, the grain size was approximately 8.2 nm. Furthermore, from the results of XRD, it was found that the crystals were cubic, and the position of the crystal peaks was consistent with that of ZnSe.

[0134] Separately from the above, ethanol was added to 20 ml of the ZnSe reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 17.5 ml of octadecene:ODE was added to disperse the precipitate.

[0135] To 17.5 mL of the dispersed ZnSe-ODE solution, 1 mL of oleic acid (OLAc) and 2 mL of trioctylphosphine (TOP) were added, and the mixture was heated with stirring at 320° C. for 10 minutes in an inert gas (N 2 ) atmosphere.

[0136] To this solution, 0.5 mL of a mixture of 0.2 mL of DDT, 0.8 mL of trioctylphosphine: TOP, and 5 mL of zinc oleate: Zn(OLAc)2 solution (0.4 M) was added, and the mixture was heated at 320° C. for 10 minutes with stirring. This operation was repeated 8 times.

[0137] Then, 2 ml of oleic acid (OLAc) was added and reacted at 320° C. for 10 minutes, and 2 ml of trioctylphosphine (TOP) was added and heated with stirring for 10 minutes at 320° C. The resulting reaction solution (ZnSe / ZnS) was cooled to room temperature.

[0138] The reaction solution thus obtained was measured using a fluorescence spectrometer, and as a result, the optical characteristics obtained were a fluorescence wavelength of about 447 nm and a fluorescence half-width of about 14 nm, as shown in FIG.

[0139] Ethanol was added to the resulting reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and hexane was added to disperse the precipitate.

[0140] ZnSe / ZnS dispersed in hexane was measured using a quantum efficiency measurement system. The fluorescence quantum yield was about 62%. The fluorescence lifetime was measured and was 16 ns.

[0141] In addition, measurements were made using a scanning electron microscope (SEM) and an X-ray diffraction (XRD) device. FIG. 12A shows the results of the scanning electron microscope (SEM), FIG. 12B shows a schematic diagram of FIG. 12A, and the solid line in FIG. 15 shows the results of the X-ray diffraction (XRD) measurements. From the SEM results, the grain size was approximately 9.8 nm. From the XRD results, the crystals were cubic. FIG. 16 shows an enlarged view of the maximum peak intensity in FIG. 15. It was found that the maximum peak intensity was shifted 0.1° to the high-angle side from the crystal peak position of ZnSe.

[0142] [Example 4] In a 100 mL reaction vessel, 291 mg of anhydrous copper acetate (Cu(OAc)), 4.8 mL of oleylamine (OLAm), and 7.75 mL of octadecene (ODE) were placed, and the mixture was heated at 150° C. for 5 minutes under an inert gas (N2) atmosphere while stirring to dissolve the raw materials.

[0143] To this solution, 1.4 mL of Se-DDT / OLAm solution (0.285 M) was added, and the mixture was heated with stirring at 150° C. for 30 minutes.

[0144] A mixture of 0.1 mL of 0.5M Te in TOP and 2.5 mL of 0.1M Se in ODE was added dropwise to the solution over 1 minute. The mixture was then heated at 150°C for 30 minutes with stirring. The resulting reaction solution (CuSeTe) was cooled to room temperature.

[0145] Then, 2682 mg of anhydrous zinc acetate: Zn(OAc), 10 mL of trioctylphosphine: TOP, and 0.4 mL of oleylamine: OLAm were added to the CuSeTe reaction solution, and the mixture was heated with stirring at 180° C. for 20 minutes under an inert gas (N 2 ) atmosphere.

[0146] Ethanol was added to the reaction solution cooled to room temperature to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 ml of octadecene (ODE) was added to disperse the precipitate.

[0147] Then, 2922 mg of anhydrous zinc acetate (Zn(OAc)), 5 mL of trioctylphosphine (TOP) and 0.5 mL of oleylamine (OLAm) were added to 12 mL of the ZnSeTe-ODE solution, and the mixture was heated under inert gas (N2) atmosphere at 180°C for 20 minutes with stirring. The resulting reaction solution (ZnSeTe) was cooled to room temperature.

[0148] Ethanol was added to 8.7 ml of the resulting ZnSeTe reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 8.75 ml of octadecene (ODE) was added to disperse the precipitate.

[0149] 0.5 mL of oleic acid (OLAc) and 1 mL of trioctylphosphine (TOP) were added to 8.75 mL of the dispersed ZnSeTe-ODE solution, and the mixture was heated with stirring at 320° C. for 10 minutes in an inert gas (N 2 ) atmosphere.

[0150] To this solution, 0.25 mL of a mixture of 0.25 mL of Se-TOP solution (1 M) and 2.5 mL of zinc oleate: Zn(OLAc)2 solution (0.4 M) was added, and the mixture was heated with stirring at 320° C. for 10 minutes. This operation was repeated six times, and then the mixture was cooled to room temperature.

[0151] The resulting ZnSeTe / ZnSe reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were a fluorescence wavelength of about 461 nm and a fluorescence half-width of about 24 nm.

[0152] [Example 5] In a 100 mL reaction vessel, 291 mg of anhydrous copper acetate (Cu(OAc)), 4.8 mL of oleylamine (OLAm), and 7.75 mL of octadecene (ODE) were placed, and the mixture was heated at 180° C. for 5 minutes under an inert gas (N2) atmosphere while stirring to dissolve the raw materials.

[0153] To this solution, 1.4 mL of Se-DDT / OLAm solution (0.285 M) was added, and the mixture was heated at 180° C. for 30 minutes with stirring.

[0154] A mixture of 0.1 mL of 0.5 M Te in TOP and 1.35 mL of 0.1 M Se in ODE was added dropwise to the solution over 1 minute. The mixture was then heated at 180° C. for 20 minutes while stirring. The resulting reaction solution (CuSeTe) was cooled to room temperature.

[0155] Then, 2682 mg of anhydrous zinc acetate: Zn(OAc), 7.5 mL of trioctylphosphine: TOP, and 0.25 mL of oleylamine: OLAm were added to the CuSeTe reaction solution, and the mixture was heated with stirring at 180° C. for 20 minutes under an inert gas (N 2 ) atmosphere.

[0156] Ethanol was added to the reaction solution cooled to room temperature to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 ml of octadecene (ODE) was added to disperse the precipitate.

[0157] Then, 2682 mg of anhydrous zinc acetate (Zn(OAc)), 7.5 mL of trioctylphosphine (TOP) and 0.25 mL of oleylamine (OLAm) were added to 12 mL of the ZnSeTe-ODE solution, and the mixture was heated under inert gas (N2) atmosphere at 180°C for 20 minutes with stirring. The resulting reaction solution (ZnSeTe) was cooled to room temperature.

[0158] Ethanol was added to 10 ml of the resulting ZnSeTe reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 8.75 ml of octadecene (ODE) was added to disperse the precipitate.

[0159] 0.5 mL of oleic acid (OLAc) and 1 mL of trioctylphosphine (TOP) were added to 8.75 mL of the dispersed ZnSeTe-ODE solution, and the mixture was heated with stirring at 320° C. for 10 minutes in an inert gas (N 2 ) atmosphere.

[0160] To this solution, 2.5 mL of a mixture of 0.25 mL of Se-TOP solution (1 M) and 5 mL of zinc oleate: Zn(OLAc)2 solution (0.4 M) was added, and the mixture was heated with stirring at 320° C. for 10 minutes. This operation was repeated four times, and then the mixture was cooled to room temperature.

[0161] The resulting ZnSeTe / ZnSe reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were a fluorescence wavelength of about 479 nm and a fluorescence half-width of about 23 nm.

[0162] Examples 1 to 5 are summarized in Table 1 below. By changing the synthesis conditions of CuSe or CuSeTe, the fluorescence half-width could be controlled to 25 nm or less and the fluorescence wavelength could be controlled within the range of 410 nm to 490 nm (preferably 420 nm to 480 nm).

[0163] [Table 1]

[0164] In Examples 1 to 3, the reaction temperature and time were increased to increase the size of the Cu2Se particles, allowing the fluorescent wavelength to be controlled. However, it was difficult to achieve a fluorescent wavelength of 450 nm or more with a ZnSe core. Therefore, CuSeTe was synthesized, and then ZnSeTe was synthesized by cation exchange, allowing the creation of fluorescent particles with a fluorescent wavelength of 460 nm or 470 nm.

[0165] The ZnSeTe quantum dots of Examples 4 and 5 are characterized in that the fluorescence half-width is 25 nm or less, and the fluorescence wavelength can be controlled within the range of 420 nm to 480 nm.

[0166] ZnSeTe quantum dots obtained by directly reacting Zn, Se, and Te have been known for some time and have a fluorescence half-width of 25 nm or more.

[0167] In Example 3 (as well as in Examples 7 and 8 described below), the fluorescence wavelength was 447 nm, and it was possible to ensure a wavelength of around 450 nm, and to obtain a high fluorescence quantum yield. When ZnSe is produced by a direct synthesis method, the particles become large and defects tend to occur inside, which tends to reduce the fluorescence quantum yield. In contrast, in Example 3, a high fluorescence quantum yield can be ensured.

[0168] It is presumed that the results of Examples 3 to 5 are all unique to cation exchange.

[0169] [Example 6] In a 100 mL reaction vessel, 182 mg of anhydrous copper acetate (Cu(OAc)2), 4.8 mL of oleylamine (OLAm), and 7.75 mL of octadecene (ODE) were placed, and the mixture was heated at 165°C for 5 minutes under an inert gas (N2) atmosphere while stirring to dissolve the raw materials.

[0170] To this solution, 1.14 mL of a Se-DDT / OLAm solution (0.7 M) was added, and the mixture was heated with stirring at 165° C. for 30 minutes. The resulting reaction solution (Cu2Se) was cooled to room temperature.

[0171] Then, 1844 mg of anhydrous zinc acetate: Zn(OAc)2, 10 mL of trioctylphosphine: TOP, and 0.4 mL of oleylamine: OLAm were added to the Cu2Se reaction solution, and the mixture was heated under inert gas (N2) atmosphere at 180°C for 45 minutes with stirring. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0172] Ethanol was added to the reaction solution cooled to room temperature to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 ml of octadecene (ODE) was added to disperse the precipitate.

[0173] Then, 12 ml of the ZnSe-ODE solution was mixed with 1844 mg of anhydrous zinc acetate (Zn(OAc)2), 10 ml of trioctylphosphine (TOP), 1 ml of oleylamine (OLAm), and 6 ml of oleic acid (OLAc), and heated at 280°C for 20 minutes under an inert gas (N2) atmosphere while stirring. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0174] The reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were a fluorescence wavelength of about 447.5 nm and a fluorescence half-width of about 14 nm.

[0175] Ethanol was added to 20 ml of the resulting ZnSe reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 17.5 ml of octadecene (ODE) was added to disperse the precipitate.

[0176] To 17.5 mL of the dispersed ZnSe-ODE solution, 1 mL of oleic acid (OLAc) and 2 mL of trioctylphosphine (TOP) were added, and the mixture was heated with stirring at 320° C. for 10 minutes in an inert gas (N 2 ) atmosphere.

[0177] To this solution, 0.5 mL of a mixture of 0.5 mL of Se-TOP solution (1 M), 0.125 mL of DDT, 0.375 mL of trioctylphosphine: TOP, and 5 mL of zinc oleate: Zn(OLAc)2 solution (0.4 M) was added, and the mixture was heated at 320° C. for 10 minutes with stirring. This operation was repeated four times.

[0178] Then, ethanol was added to the obtained reaction liquid to generate a precipitate, which was then centrifuged to recover the precipitate. 17.5 ml of octadecene (ODE) was added to the precipitate to disperse it, and 1 ml of oleic acid (OLAc) and 2 ml of trioctylphosphine (TOP) were added in the same manner as above, and the mixture was heated with stirring at 320°C for 10 minutes in an inert gas (N2) atmosphere.

[0179] To this solution, 0.5 mL of a mixture of 0.5 mL of DDT, 1.5 mL of trioctylphosphine: TOP, and 10 mL of zinc oleate: Zn(OLAc)2 solution (0.4 M) was added, and the mixture was heated at 320° C. for 10 minutes with stirring. This operation was repeated 10 times.

[0180] (A) Ethanol was then added to the resulting reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate. 17.5 ml of octadecene (ODE) was added to the precipitate to disperse it, and 1 ml of oleic acid (OLAc) and 2 ml of trioctylphosphine (TOP) were added in the same manner as above. The mixture was then heated with stirring at 320°C for 10 minutes in an inert gas (N2) atmosphere.

[0181] (B) 0.5 mL of a mixture of 0.5 mL of DDT, 1.5 mL of trioctylphosphine: TOP, and 10 mL of zinc oleate: Zn(OLAc)2 solution (0.4 M) was added to this solution, and the mixture was heated at 320°C for 10 minutes with stirring. This operation was repeated six times. Then, the mixture was heated at 320°C for 30 minutes with stirring.

[0182] Thereafter, the above-mentioned washing and coating procedures (A) and (B) were repeated three times to obtain the final reaction solution (ZnSe / ZnS), which was the target product, and the solution was cooled to room temperature.

[0183] The reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were a fluorescence wavelength of about 444 nm and a fluorescence half-width of about 15 nm.

[0184] Ethanol was added to the resulting reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and hexane was added to disperse the precipitate.

[0185] ZnSe / ZnS dispersed in hexane was measured using a quantum efficiency measurement system. The fluorescence quantum yield was about 62%. The fluorescence lifetime was measured and was 15ns.

[0186] [Example 7] In a 100 mL reaction vessel, 182 mg of anhydrous copper acetate (Cu(OAc)2), 4.8 mL of oleylamine (OLAm), and 7.75 mL of octadecene (ODE) were placed, and the mixture was heated at 165°C for 5 minutes under an inert gas (N2) atmosphere while stirring to dissolve the raw materials.

[0187] To this solution, 1.14 mL of a Se-DDT / OLAm solution (0.7 M) was added, and the mixture was heated with stirring at 165° C. for 30 minutes. The resulting reaction solution (Cu2Se) was cooled to room temperature.

[0188] Then, 1844 mg of anhydrous zinc acetate: Zn(OAc)2, 10 mL of trioctylphosphine: TOP, and 0.4 mL of oleylamine: OLAm were added to the Cu2Se reaction solution, and the mixture was heated under inert gas (N2) atmosphere at 180°C for 45 minutes with stirring. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0189] Ethanol was added to the reaction solution cooled to room temperature to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 ml of octadecene (ODE) was added to disperse the precipitate.

[0190] Then, 12 ml of the ZnSe-ODE solution was mixed with 1844 mg of anhydrous zinc acetate (Zn(OAc)2), 10 ml of trioctylphosphine (TOP), 1 ml of oleylamine (OLAm), and 6 ml of oleic acid (OLAc), and heated at 280°C for 20 minutes under an inert gas (N2) atmosphere while stirring. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0191] The reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were a fluorescence wavelength of about 447.5 nm and a fluorescence half-width of about 14 nm.

[0192] Ethanol was added to 20 ml of the resulting ZnSe reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 17.5 ml of octadecene (ODE) was added to disperse the precipitate.

[0193] To 17.5 mL of the dispersed ZnSe-ODE solution, 1 mL of oleic acid (OLAc) and 2 mL of trioctylphosphine (TOP) were added, and the mixture was heated with stirring at 320° C. for 10 minutes in an inert gas (N 2 ) atmosphere.

[0194] To this solution, 0.5 mL of a mixture of 0.5 mL of Se-TOP solution (1 M), 0.125 mL of DDT, 0.375 mL of trioctylphosphine: TOP, and 5 mL of zinc oleate: Zn(OLAc)2 solution (0.4 M) was added, and the mixture was heated at 320° C. for 10 minutes with stirring. This operation was repeated four times.

[0195] Then, ethanol was added to the obtained reaction liquid to generate a precipitate, which was then centrifuged to recover the precipitate. 17.5 ml of octadecene (ODE) was added to the precipitate to disperse it, and 1 ml of oleic acid (OLAc) and 2 ml of trioctylphosphine (TOP) were added in the same manner as above, and the mixture was heated with stirring at 320°C for 10 minutes in an inert gas (N2) atmosphere.

[0196] To this solution, 0.5 mL of a mixture of 0.5 mL of DDT, 1.5 mL of trioctylphosphine: TOP, and 10 mL of zinc oleate: Zn(OLAc)2 solution (0.4 M) was added, and the mixture was heated at 320° C. for 10 minutes with stirring. This operation was repeated 10 times.

[0197] (C) Then, ethanol was added to the reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate. 17.5 ml of octadecene (ODE) was added to the precipitate to disperse it, and 1 ml of oleic acid (OLAc) and 2 ml of trioctylphosphine (TOP) were added in the same manner as above. The mixture was then heated with stirring at 320°C for 10 minutes in an inert gas (N2) atmosphere.

[0198] (D) 0.5 mL of a mixture of 0.5 mL of DDT, 1.5 mL of trioctylphosphine: TOP, and 10 mL of zinc oleate: Zn(OLAc)2 solution (0.4 M) was added to this solution, and the mixture was heated at 320°C for 10 minutes with stirring. This operation was repeated six times. Then, the mixture was heated at 320°C for 30 minutes with stirring.

[0199] Thereafter, the reaction solution was subjected to the above washing and coating procedures (C) and (D) twice.

[0200] Then, ethanol was added to the obtained reaction liquid to generate a precipitate, which was then centrifuged to recover the precipitate. 17.5 ml of octadecene (ODE) was added to the precipitate to disperse it, and 1 ml of oleic acid (OLAc) and 2 ml of trioctylphosphine (TOP) were added in the same manner as above, and the mixture was heated with stirring at 320°C for 10 minutes in an inert gas (N2) atmosphere.

[0201] To this solution, 0.5 mL of a mixture of 0.5 mL of DDT, 1.5 mL of trioctylphosphine: TOP, and 10 mL of zinc oleate: Zn(OLAc)2 solution (0.4 M) was added, and the mixture was heated at 320°C for 10 minutes with stirring. This operation was repeated six times. Then, the mixture was heated at 320°C for 30 minutes with stirring.

[0202] (E) 1.0 mL of a mixture of 0.25 mL of DDT, 0.75 mL of TOP, and 5 mL of 0.4 M ZnBr2 in oleic acid·TOP was added to this solution, and the mixture was heated at 320°C for 10 minutes. The final reaction solution (ZnSe / ZnS) was obtained, and cooled to room temperature.

[0203] The reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were a fluorescence wavelength of about 444 nm and a fluorescence half-width of about 15 nm.

[0204] Ethanol was added to the resulting reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and hexane was added to disperse the precipitate.

[0205] ZnSe / ZnS dispersed in hexane was measured using a quantum efficiency measurement system. The fluorescence quantum yield was approximately 76%. The fluorescence lifetime was also measured and found to be 17ns. Elemental analysis (EDX) showed the following: Zn: 53 atom% Se: 16 atom% S: 23 atom% Br: 1 atom%

[0206] [Example 8] The fluorescence quantum yield of ZnSe / ZnS obtained by carrying out the same procedure as in [Example 7] (E) was 80%, except that ZnBr2 was changed to ZnCl2.

[0207] [Example 9] The fluorescence quantum yield of ZnSe / ZnS obtained by carrying out the same procedure as in [Example 7] (E) was 69%, except that ZnBr2 was changed to ZnI2.

[0208] In Examples 7 to 9, it was found that by coating a 445 nm ZnSe core with ZnS and then adding a solution containing zinc halide, the fluorescence quantum yield was improved by about 7% to 18% compared to Example 6 (see Table 2 below). In addition, as a result of analyzing the composition after washing the QD obtained in Example 7, bromine (Br) was detected, which suggests that the surface was modified with a halogen, and that this effect improved the fluorescence quantum yield.

[0209] [Table 2]

[0210] [Comparative Example 1] In a 100 mL reaction vessel, 0.833 mL of zinc oleate: Zn(OLAc)2-ODE solution (0.4 M) and 10 mL of Se-ODE solution (0.1 M) were placed and heated with stirring at 280°C for 35 minutes under an inert gas (N2) atmosphere.

[0211] The reaction solution thus obtained was measured using a fluorescence spectrometer, and the optical characteristics were that the fluorescence wavelength was about 455.0 nm and the fluorescence half-width was about 45.2 nm.

[0212] [Comparative Example 2] In a 300 mL reaction vessel, 182 mg of anhydrous copper acetate (Cu(OAc)2), 7.75 mL of oleylamine (OLAm), and 4.8 mL of octadecene (ODE) were placed, and the mixture was heated at 150° C. for 10 minutes under an inert gas (N2) atmosphere while stirring to dissolve the raw materials.

[0213] To this solution, 2.8 mL of a Se-DDT / OLAm solution (0.285 M) was added, and the mixture was heated with stirring at 150° C. for 30 minutes. The resulting reaction solution (CuSe) was cooled to room temperature.

[0214] Then, 20.682 g of anhydrous zinc acetate: Zn(OAc), 10 mL of trioctylphosphine: TOP, and 0.4 mL of oleylamine: OLAm were added to the CuSe reaction solution, and the mixture was heated under inert gas (N2) atmosphere at 180°C for 30 minutes with stirring. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0215] Ethanol was added to the reaction solution cooled to room temperature to generate a precipitate, which was then centrifuged to recover the precipitate, and 24 ml of octadecene (ODE) was added to disperse the precipitate.

[0216] Then, 20.682 g of anhydrous zinc acetate (Zn(OAc)), 10 mL of trioctylphosphine (TOP) and 1 mL of oleylamine (OLAm) were added to 24 mL of the ZnSe-ODE solution, and the mixture was heated under inert gas (N2) atmosphere at 180°C for 30 minutes with stirring. The resulting reaction solution (ZnSe) was cooled to room temperature.

[0217] The reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were a fluorescence wavelength of about 438.5 nm and a fluorescence half-width of about 13 nm.

[0218] The reaction solution was measured using a quantum efficiency measurement system. The fluorescence quantum yield was found to be about 11%. The fluorescence lifetime was also measured to be 43 ns.

[0219] Ethanol was added to 20 ml of the above ZnSe reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 17.5 ml of octadecene:ODE was added to disperse the precipitate.

[0220] 17.5 mL of the dispersed ZnSe-ODE solution was heated under inert gas (N2) atmosphere at 310°C for 20 minutes with stirring.

[0221] To this solution, 0.545 mL of a mixture of 0.73 mL of S-TOP solution (2.2 M) and 3.63 mL of zinc oleate: Zn(OLAc)2 solution (0.8 M) was added, and the mixture was heated at 310°C for 10 minutes with stirring. This operation was repeated 8 times. The resulting reaction solution (ZnSe / ZnS) was cooled to room temperature.

[0222] Ethanol was added to the resulting reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and hexane was added to disperse the precipitate.

[0223] The hexane-dispersed ZnSe / ZnS was measured using a fluorescence spectrometer. As a result, the optical characteristics were obtained as shown in Figure 4, with a fluorescence wavelength of about 437.5 nm and a fluorescence half-width of about 13.8 nm.

[0224] The same solution was measured using a quantum efficiency measurement system, and the fluorescence quantum yield was found to be about 33%. The fluorescence lifetime was also measured to be 44 ns.

[0225] In addition, an experiment was carried out to estimate the optimal number of coating additions in Example 1 from the change in the fluorescence lifetime and the number of coating additions. The results are shown in Table 3 below.

[0226] [Table 3]

[0227] From this, it can be predicted that the optimal number of coating additions is 6 to 8 times, at which the fluorescence quantum yield is high and the fluorescence lifetime is short. This varies depending on the coating method, but when confirmed from the particle size, the same tendency is seen for all materials. In this way, all of the present examples are examined so that the coating thickness (particle size) is maximized when the fluorescence quantum efficiency is the highest and the fluorescence lifetime is shortest.

[0228] In the above experiments, Example 1 and Comparative Example 2 use S-TOP as a sulfur source when coating the shell (ZnS). This was effective for the ZnSe of Example 1, which has a small particle size (short fluorescent wavelength), but was not suitable for Comparative Example 2, which has a fluorescent wavelength of about 440 nm, and it was found that the particle shape was deteriorated and the fluorescent quantum yield after coating was also low.

[0229] In contrast, in Example 6, the sulfur source was changed to DDT. As a result, it was found that good fluorescence yield and particle shape could be maintained at a fluorescence wavelength of 440 nm or more, and ZnS could be coated. The above contents are summarized in Table 4 below.

[0230] [Table 4]

[0231] From the above experimental results, it was found that in each Example, the particle size of the quantum dots could be adjusted within the range of 5 nm to 20 nm. It was also found that in each Example, the fluorescence quantum yield was 5% or more and the fluorescence half-width was 25 nm or less. It was also found that the fluorescence lifetime could be reduced to 50 ns or less. It was also found that the fluorescence wavelength could be adjusted within the range of 410 nm to 490 nm. It was also found that in the core-shell structure consisting of Zn, Se, and S, the maximum intensity peak position in XRD was 0.05° to 1.2° higher than the crystal peak of the ZnSe core alone.

[0232] This peak shift to the higher angle side indicates that the lattice constant has changed by coating the ZnSe core with ZnS. Furthermore, the results show that the amount of this peak shift is proportional to the amount of ZnS coating. In addition, in this result, the position of the XRD is extremely close to the ZnS peak position, but blue light (430-455 nm) is emitted, which suggests that the core is ZnSe and that ZnS is coated on top of it.

[0233] In other words, based on the peak shift and blue emission from the ZnSe core, it can be inferred that the core-shell structure is composed of Zn, Se, and S. [Industrial Applicability]

[0234] According to the present invention, quantum dots that emit blue fluorescence can be stably obtained. By applying the quantum dots of the present invention to LEDs, backlight devices, display devices, etc., excellent light emission characteristics can be obtained in each device.

[0235] This application is based on Japanese Patent Application No. 2019-170996 filed on September 20, 2019 and Japanese Patent Application No. 2020-024688 filed on February 17, 2020, the contents of which are incorporated herein in their entirety.

Claims

1. A core-shell structure having a core containing Zn and Se and a shell containing Zn and S, The particle size is 5 nm or more and 20 nm or less, The surface of the shell is modified with a halogen. A quantum dot characterized by:

2. 2. The quantum dot according to claim 1, wherein the fluorescence half-width is 25 nm or less.

3. 3. The quantum dot according to claim 1, wherein the fluorescence wavelength is in the range of 410 nm to 490 nm.

4. 4. The quantum dot according to claim 1, wherein the particle shape is polygonal.

5. synthesizing a copper chalcogenide precursor from an organic copper compound or an inorganic copper compound and an organic chalcogen compound, and synthesizing a core-shell quantum dot having a core containing Zn and Se and a shell containing Zn and S using the copper chalcogenide precursor; thereafter, adding a solution containing zinc halide; modifying the surface of the shell with a halogen; having A method for producing quantum dots comprising the steps of:

6. 6. The method for producing quantum dots according to claim 5, wherein the Cu and Zn of the copper chalcogenide precursor are metal-exchanged.

7. 7. The method for producing quantum dots according to claim 6, wherein the metal exchange reaction is carried out at a temperature of 150° C. or higher and 300° C. or lower.

Citation Information

Patent Citations

  • Preparation method of non-cadmium base water-soluble core-shell structure quantum dot and application of quantum dot in silver nanowire light-emitting transparent conductive films

    CN104592990A

  • Quantum dot and preparation method thereof

    CN108795412A

  • Semiconductor nanocrystal particle, production method thereof, population thereof, and electroluminescent element

    JP2019145505A

  • Electroluminescent display device

    US20190280231A1

  • Quantum dot, wavelength conversion member using quantum dot, illumination member, backlight device, display device, and method for manufacturing quantum dot

    WO2019022217A1